EFFECT OF PLANT GROWTH REGULATOR APPLICATION AT DIFFERENT GROWTH STAGES ON THE ECONOMICAL YIELD POTENTIAL OF COARSE RICE (Oryza Sativa L.) - I. Bakhsh; I. Awan; M. Sadiq; M. Niamatullah; K. U. Zaman; M. Aftab (Journal of Animal and Plant Sciences, 2011)
The study was conducted to find out the growth behaviour of transplanted coarse rice (IR-6) as influenced by plant growth regulator (NAA) under the agro climatic conditions of Dera Ismail Khan, Pakistan, during 2004 and 2005 using Randomized Complete Block Design with split plot arrangements. Main plot consisted of three critical growth stages of paddy rice, namely S1 (tillering) S2 (panicle initiation) and S3 (grain formation stage), while sub plot contained four levels of 0, 60, 90 and 120 ml ha-1 of plant growth regulator (Naphthalene Acetic Acid). The data was recorded on plant height (cm) at maturity, number of panicle   (m-2), number of spikelets panicle-1, 1000-grain weight (g) and paddy yield (Mg ha-1). The effect of plant growth regulator levels, growth stages of paddy rice and interactions between them were found highly significant (LSD, p < 0.01) in term of enhancement in paddy yield and yield components. The application of plant growth regulator @ 90 ml ha-1 at the stage of panicle initiation proved most beneficial in terms of attaining 130.4 cm and 130 cm as maximum plant height, 324.5 m2 and 328 m2 as highest number of panicles, 164.3 and 168.5 as maximum number of spikelets panical-1, 78.5% and 80.5% as maximum normal kernels, 20.76g and 21.02g as higher 1000-grain weight, 7.65 Mg ha-1 as economical paddy yield during 2004 and 2005 respectively.
Keywords: Rice; Stages; Plant Growth Regulator; Naphthalene Acetic Acid.